From Heart to Heart: An Empirical-Synthesis of a Muslim’s Donation Cycle - Faza, Firdan Thoriq; Indriani, Astiwi (EQUILIBRIUM, 2022)
This research contributes to the theory of giving behavior from the perspective of Islamic religiosity by describing how an individual Muslim makes donations from the initial intention, manages their finances and savings, and impacts their intrinsic satisfaction and religious beliefs. Descriptive qualitative research was conducted with case studies to describe the dynamics of a series of decisions made by individuals based on their experience of giving donations. The analytical methodology uses a descriptive qualitative narrative type technique taken from in-depth interviews until the data sample is saturated by respondents in Semarang, Indonesia. Twelve respondents were selected based on their experience in donating, the amount of the donation and the variation in their ages. The study results show that individuals who have religious awareness will have a strong desire to help other people or their community because they comply with religious observance guidelines. In addition, donations are helpful because they can provide an experience of gratitude, intrinsic satifaction, creating a sense of security from evil to have a continuous donation cycle. This research produces a synthesis in a cycle model between religiosity, donation, and intrinsic satisfaction.